Identification of Anthrax in Endemic Areas in South Sulawesi Province - Sartika Juwita; Purwanta Purwanta; Muflihanah Muflihanah; Titis Furi Djatmikowati (Hasanuddin University, 2018)
Anthrax is a strategic and important disease because it is a zoonotic disease which caused death and difficult to eradicate because it produces spores. The aim of the study was to identify anthrax in endemic areas in South Sulawesi Province. Soil samples obtained from Gowa and Pinrang regency were examined by bacterial culture test and then positive results from bacterial culture followed by multiplex PCR. Based on the results of the isolation of 52 soil samples show 35 samples from Pinrang regency show all negative anthrax, while from 17 soil samples from Gowa regency show 2 positive samples of anthrax. Positive samples of anthrax were from Timbuseng village, Patallasang district, Gowa regency. The results continued with PCR technique using Bacillus anthracis colonies derived from positive soil samples. It showed the virulent strain of Bacillus anthracis. A virulent strain is indicated by a DNA fragment of a pXO1 plasmid encoding a toxin lethal factor (Lef) of 385 bp and a DNA fragment of a pXO2 plasmid encoding a capsule of anthrax (Cap) of 264 bp and also common bacterial markers of the Bacillus genome chromosome (Ba183) of 152 bp.